Inflammatory profile of incident cases of late-onset compared with young-onset rheumatoid arthritis: A nested cohort study - Mena-Vázquez, Natalia; Lisbona-Montañez, Jose Manuel; Redondo-Rodriguez, Rocío; Mucientes, Arkaitz; Manrique-Arija, Sara; Rioja, José; Garcia-Studer, Aimara; Ortiz-Márquez, Fernando; Cano-García, Laura; Fernández-Nebro, Antonio (Frontiers in Medicine, 2022)
Objectives: To describe the characteristics of patients between late-onset rheumatoid arthritis (LORA) with young-onset rheumatoid arthritis (YORA), and analyze their association with cumulative inflammatory burden. Methods: We performed a nested cohort study in an inception cohort comprising 110 patients with rheumatoid arthritis (RA) and 110 age- and sex-matched controls. The main variable was cumulative inflammatory activity according to the 28-joint Disease Activity Score with erythrocyte sedimentation rate (DAS28-ESR). High activity was defined as DAS28 ≥3.2 and low activity as DAS28 <3.2. The other variables recorded were inflammatory cytokines, physical function, and comorbid conditions. Two multivariate models were run to identify factors associated with cumulative inflammatory activity. Results: A total of 22/110 patients (20%) met the criteria for LORA (≥60 years). Patients with LORA more frequently had comorbid conditions than patients with YORA and controls. Compared with YORA patients, more LORA patients had cumulative high inflammatory activity from onset (13 [59%] vs 28 [31%]; p=0.018) and high values for CRP (p=0.039) and IL-6 (p=0.045). Cumulative high inflammatory activity in patients with RA was associated with LORA (OR [95% CI] 4.69 [1.49-10.71]; p=0.008), smoking (OR [95% CI] 2.07 [1.13-3.78]; p=0.017), anti–citrullinated peptide antibody (OR [95% CI] 3.24 [1.15-9.13]; p=0.025), average HAQ score (OR [95% CI] 2.09 [1.03-14.23]; p=0.034), and physical activity (OR [95% CI] 0.99 [0.99-0.99]; p=0.010). The second model revealed similar associations with inflammatory activity in patients with LORA. Conclusion: Control of inflammation after diagnosis is poorer and comorbidity more frequent in patients with LORA than in YORA patients and healthy controls.